2020
DOI: 10.1007/s00438-020-01732-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the AGL1 aegerolysin in the mycoparasitic fungus Trichoderma atroviride reveals a role in conidiation and antagonism

Abstract: Aegerolysins are small secreted pore-forming proteins that are found in both prokaryotes and eukaryotes. The role of aegerolysins in sporulation, fruit body formation, and in lysis of cellular membrane is suggested in fungi. The aim of the present study was to characterize the biological function of the aegerolysin gene agl1 in the mycoparasitic fungus Trichoderma atroviride, used for biological control of plant diseases. Gene expression analysis showed higher expression of agl1 during conidiation and during g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…Many studies showed that Trichoderma spp. exhibited mycoparasitic capacity against R. solani ( Geremia et al, 1993 ; De La Cruz et al, 1995 ; Lorito et al, 1998 ; Kubicek et al, 2011 ; Dubey et al, 2021 ). Trichoderma spp.…”
Section: Trichoderma Spp Genes Involved In Mycoparasitismmentioning
confidence: 99%
“…Many studies showed that Trichoderma spp. exhibited mycoparasitic capacity against R. solani ( Geremia et al, 1993 ; De La Cruz et al, 1995 ; Lorito et al, 1998 ; Kubicek et al, 2011 ; Dubey et al, 2021 ). Trichoderma spp.…”
Section: Trichoderma Spp Genes Involved In Mycoparasitismmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1 : The mycological journals; Table S2: Proportion of women authors publishing by research discipline; Table S3: Proportion of women researchers publishing by author position in microbiology; Table S4: Proportion of women researchers publishing by author position in mycology; Table S5: Research of fungal aegerolysins as published in scientific journals and disciplines; Table S6: Status of women researchers; Table S7: Region of women researchers; Table S8: Descriptors of fungal research area by women researchers; Table S9: Keywords women researchers use at least twice to describe their fungal research area; Table S10: Gender breakdown of plenary and selected speakers, session chairs, and meeting organizers for two alternating meetings FGC and ECFG; References [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%
“…B. cinerea causes grey mold in over 200 plant species, including a large number of crops, and is difficult to control because of its survival ability under unfavorable conditions, such as low temperature. However, low-temperature resistance biocontrol Trichoderma strains against B. cinerea are few in number at present [36][37][38][39][40]. In this study, Trichoderma C5-9 was demonstrated to directly suppress the pathogen B. cinerea growth under lowtemperature conditions in a dual-culture assay.…”
Section: Discussionmentioning
confidence: 87%